Exploring the experiences of parent caregivers of children with chronic medical complexity during pediatric intensive care unit hospitalization: an interpretive descriptive study - Janet E. Rennick; Isabelle St-Sauveur; Alyssa M. Knox; Margaret Ruddy (BMC, 2019)
Abstract Background Children with medical complexity (CMC) account for an increasing proportion of pediatric intensive care unit (PICU) admissions across North America. Their risk of unscheduled PICU admission is threefold compared to healthy children, and they are at higher risk of prolonged length of stay and PICU mortality. As a result of their sophisticated home care needs, parents typically develop significant expertise in managing their children's symptoms and tending to their complex care needs at home. This can present unique challenges in the PICU, where staff may not take parents' advanced expertise into account when caring for CMC. The study aimed to explore the experiences of parents of CMC during PICU admission. Methods This interpretive descriptive study was performed in the PICU of one Canadian, quaternary care pediatric hospital. Semi-structured interviews were conducted with 17 parent caregivers of 14 CMC admitted over a 1-year period. Results Parents of CMC expected to continue providing expert care during PICU admission, but felt their knowledge and expertise were not always recognized by staff. They emphasized the importance of parent-staff partnerships. Four themes were identified: (1) "We know our child best;" (2) When expertise collides; (3) Negotiating caregiving boundaries; and (4) The importance of being known. Results support the need for a PICU caregiving approach for CMC that recognizes parent expertise. Conclusions Partnership between staff and parents is essential, particularly in the case of CMC, whose parents are themselves skilled caregivers. In addition to enhanced partnerships with health care professionals, needs expressed by parents of CMC during PICU hospitalization included improved communication with staff, and more attention to continuity of care in the PICU and across hospital services. Parent-staff partnerships must be informed by ongoing communication and negotiation of caregiving roles throughout the course of the child's PICU hospitalization.